Práticas de gestão da polícia militar do estado de São Paulo e a saúde do trabalhador - Martingo, Liszeila Reis Abdala (2014)
Introduction: The management models adopted in the area of public safety mainly aim at the quality and productivity of services offered to the population. What is still unclear is how these managerial changes affect the life, health and work conditions of military police officers. Objective: to assess the effects of the management model adopted by the Military Police of São Paulo on the quality of life and working conditions of a sample of public safety workers. Methods: This is a descriptive, exploratory, quantitative study on the relationship between company management and life and health conditions of 57 military policemen. We analyzed four domains: physical, psychological, social and environmental. For data collection we used the WHOQOL Brief (Brazilian version) and a socio-economic questionnaire. Results: As for socio-demographic characteristics, we found that: 86% were male; 83.9% were married; 77.2% were non-commissioned officers; 87.7% performed support functions; 70.4% were active. Regarding the quality of life, the respondents reported difficulties related to safety, noise and pollution; the financial situation; leisure; housing conditions; and access to transportation and health care utilization. Conclusion: The obtained data show the relevance of the changes in the management model for the quality of life of the military police officers who participated in this study and the need for further research in this context.